Revisiting Ritual and Ancestral Practice: Belief and Belonging within the Jamasan Bende Tradition in Bumijawa Tegal, Central Java - Luthfi Rahman; Gita Fajriyani; Pahlevi Nova Triani; Ednan Aslan (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2022)
This study focuses on religio-cultural values and meanings within the ritual of Jamasan Bende (Bende washing) on 10th Rabi’ul Awal in Bumijawa, Tegal, Central Java, Indonesia. The topic is interesting as religious and cultural values intermingle within a local practice. It can be seen from how the ritual is accompanied by the recitation of the holy verses of the Qur'an. It signifies that ancient ritual traditions have begun to fade in society because they are considered to contain mystical beliefs and heretical elements handed down from the inhabitants’ ancestors. However, the successors have been trying to advocate and revitalize it instead of abolishing it. It is qualitative research that serving as a field study. The approach used in this research is phenomenology. It digs deeper into interviewing people practicing the ritual and documenting things concerning it. It employs magi theory and theoretical stances from Marshall’s ritual theory that heavily focuses on the issue of religious ritual simultaneously.